Pseudomonas aeruginosa : genotipagem, alterações estruturais e expressão gênica diferencial após exposição à combinação de meropenem e ciprofloxacino - Siqueira, Vera Lúcia Dias (2013)
The use of antimicrobial combinations for the treatment of Pseudomonas aeruginosa infection is common in clinical practice. However, the mechanism of action of these combinations remains largely unknown. The present study identified structural changes and differentially expressed genes in a genotypically distinct multi-drug resistant P. aeruginosa clinical isolate (1071-MRPA) caused by exposure to subinibitory concentrations of meropenem and ciprofloxacin alone and in combination (MCC). The results of this study were compiled into two manuscripts presented in Chapter II. Initially, P. aeruginosa isolates were obtained from patients in a university hospital in Maringá, Paraná, Brazil, from January 2007 to July 2009. The isolates were genotyped by enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR). Thirty-two genetically distinct multidrug-resistant P. aeruginosa isolates and P. aeruginosa isolates resistant to at least one of two antimicrobials, were selected for the in vitro determination of the antimicrobial action of the MCC. This combination was synergistic to 25.0% and 40.6% of the P. aeruginosa isolates tested by checkerboard and time-kill curve assays, respectively. Subsequently, because of the synergistic action of the MCC in 1071-MRPA, structural changes were assessed by scanning and transmission electron microscopy and gene expression using Representational Difference Analysis (RDA) and quantitative real-time PCR (qPCR). Electron microscopy indicated that the MCC caused a summation of the structural and morphological changes induced by the antimicrobials alone in 1071-MRPA. However, outer membrane vesicles that are normally related to the bacterial SOS response and cytotoxic effects in the host were greater amount with ciprofloxacin exposure and significantly inhibited in MCC-exposed cells. Genes related to cell-wall and DNA repair, among others, were differentially expressed in meropenem-, ciprofloxacin-, and MCC-exposed 1071-MRPA. Additionally, qPCR analysis revealed that besides of differentially expressed genes, associated with DNA and cell wall repair, genes related to bacterial SOS response regulation and antimicrobial resistance exhibited lower expression in MCC-exposed cells. The present study suggests that the MCC may be an alternative for the treatment of infections caused by P. aeruginosa. The effect of this antimicrobial combination may be not only the result of a summation of the effects of meropenem and ciprofloxacin but also a result of differential action that likely affects protective mechanisms in the bacteria.